(untitled) ("Temas Sociais" Journal, 2022)
This article presents a study that sought to socio-affectively characterize the male victim of domestic violence in shelter situations in Portugal and to identify the perception of the Victim Support Technician (TAV) when confronted with domestic violence against men. We used a qualitative-quantitative methodological approach, using different instruments for data collection, the semi-structured interview and the questionnaire survey. The sample comprises two groups, eight male victims of domestic violence, in shelter, in the “Casa Abrigo para Homens” and 30 TAV from APAV. Some of the most relevant results obtained show that most men who are victims of domestic violence have some type of physical fragility, show a lot of resistance to reporting, and the feeling of fear, humiliation and shame persist in most cases. The characterization and profile of these victims in the national context proved to be still unknown, namely by the technicians specialized in the matter. The supports available to this male victim are not equivalent to those available to women.